The saccharibacterium TM7x elicits differential responses across its host range - Utter, Daniel R.; He, Xuesong; Cavanaugh, Colleen M.; McLean, Jeffrey S.; Bor, Batbileg (The ISME Journal, 2020)
Host range is a fundamental component of symbiotic interactions, yet it remains poorly characterized for the prevalent yet enigmatic subcategory of bacteria/bacteria symbioses. The recently characterized obligate bacterial epibiont Candidatus Nanosynbacter lyticus TM7x with its bacterial host Actinomyces odontolyticus XH001 offers an ideal system to study such a novel relationship. In this study, the host range of TM7x was investigated by coculturing TM7x with various related Actinomyces strains and characterizing their growth dynamics from initial infection through subsequent co-passages. Of the twenty-seven tested Actinomyces , thirteen strains, including XH001, could host TM7x, and further classified into “permissive” and “nonpermissive” based on their varying initial responses to TM7x. Ten permissive strains exhibited growth/crash/recovery phases following TM7x infection, with crash timing and extent dependent on initial TM7x dosage. Meanwhile, three nonpermissive strains hosted TM7x without a growth-crash phase despite high TM7x dosage. The physical association of TM7x with all hosts, including nonpermissive strains, was confirmed by microscopy. Comparative genomic analyses revealed distinguishing genomic features between permissive and nonpermissive hosts. Our results expand the concept of host range beyond a binary to a wider spectrum, and the varying susceptibility of Actinomyces strains to TM7x underscores how small genetic differences between hosts can underly divergent selective trajectories.